Digital Gamified Learning in Teacher Education: Insights from Pre-service Teachers in Kasaragod District - Thiyagu, K (Voices of Teachers and Teacher Educators, 2026)
This study adopts a descriptive survey methodology to examine the awareness, experiences, and perceptions of B.Ed. trainees regarding digital gamified learning (DGL) in the Kasaragod district of Kerala. The research seeks to explore pre-service teachers’ familiarity with DGL, their first-hand experiences, levels of interest, and preferred digital devices for engaging in such learning approaches. The findings reveal varying levels of familiarity among the participants, along with a generally high interest in DGL, despite limited and inconsistent practical exposure. Smartphones and laptops emerged as the most preferred devices for accessing gamified learning resources. Overall, the respondents demonstrated a positive attitude towards DGL, recognizing its potential relevance and usefulness in future educational settings. However, the study underscores the need for greater training opportunities and increased exposure to effectively integrate and utilize DGL within educational frameworks.